Prevalence, Severity and Burden of Post-Traumatic Stress Disorder in Black Men and Women Across the Adult Life span. (June 2022) - Jones, Audrey L.; Rafferty, Jane; Cochran, Susan D.; Abelson, Jamie; Hanna, Matthew R.; Mays, Vickie M.
Objectives: To examine post-traumatic stress disorder (PTSD) among Black adults in younger, middle, and older ages.Methods: Using nationally representative data from the National Survey of American Life, we estimated lifetime and 12-month prevalence of PTSD in Black men and women ages 18–34, 35–49, and 50+. We determined PTSD persistence and severity by age group, then associations of PTSD with socio-economic status, chronic stress, and racial discrimination in middle age.Results: The lifetime prevalence of PTSD was higher in Black women/men ages 18–34 (prevalence=14.0%/6.3%) and 35–49 (12.8%/4.6%) versus 50 and older (8.7%/5.1%). Those ages 35–49 were more likely than younger/older Black adults to have severe interference in work, relationships, and activities domains. In middle age, PTSD was associated with unemployment, lower education, poverty, and stress in Black men, and unemployment, divorce, poverty, stress, and discrimination in Black women.Discussion: Black women experience a disproportionate burden of PTSD in middle age.